Insights on the Film Tourism and Archéocinema for the Promotion of Heritage Tourism: A Critical Review - Haddad, Naif Adel (Global Journal of Cultural Studies, 2023)
The link between Cultural Heritage (CH), media, and film tourism has gained increasing attention in the literature over the last two decades. The 21st-century film tourism industry edutainment must reflect the experiences of 21st-century digital/virtual requirements. Film tourism is often considered a potential marketing channel for World Heritage Sites (WHS) and CH tourism. Limited research addresses how heritage film tourism providers employ and deal with the film industry and Archéocinema media for marketing communication. This paper attempts to discuss the relationship between the capability of heritage film tourism as a promotional tool combined with Archéocinema in constructing the optimistic destination image of heritage tourism and experience as it flows in both physical places and virtual environments. It argues that both environments, as dynamic and generate meanings, merge, and embody subjectivity and objectivity now in one process. This process suggests building a critical, informative, and promotional purpose by engaging in storyline and storytelling, learning about what and how film tourism and Archéocinema can offer and representing it in a modern key within and beyond the physical dimensions of place in an ethical and transparent approach according to the London Charter and the Seville Principles.